Outcomes of Early Vs. Delayed Laparoscopic Cholecystectomy in Acute Biliary Stone-Induced Pancreatitis a Prospective Observational Study - Musarrat Hussain, Jamshed Alam, Muhib Ullah, Muhammad Jawad Zahid, Uzma Wahid (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aims to compare the outcomes of early and delayed laparoscopic cholecystectomy in patients with acute biliary stone-induced pancreatitis Methods: this prospective observational stusy conducted in department of surgery hmc Peshawar From January 2015 to December 2019, 200 patients (100) (50%) male and 100(50%) female) with acute biliary stone-induced pancreatitis underwent laparoscopic cholecystectomy. Hospital E.M.R.s provided patient data. Laparoscopic cholecystectomy was performed early (before 72 hours) or delayed (beyond 72 hours). Complications and death were crucial outcomes. Recovery, hospitalization, and postoperative discomfort were secondary outcomes. Chi-square and t-tests analyzed data. Results: 200 patients were evaluated with a median age of 45 (IQR=35-56) years. 43 (21.5%) patients had difficult dissection. The median operative time was 46 (IQR=37-55) minutes, while the median hospital stay was 8 (IQR=5-8) days. 65(32.5%) patients had drain placement. Only minor complications were seen in 22 (11%) patients. Furthermore, most of the patients in the gallbladder group, i.e., 90.5%, had complete recovery, while the mortality rate was also meager, i.e., 0.45%. Early laparoscopic cholecystectomy had a reduced incidence of complications (p<0.05), shorter inpatient time (p<0.001), and quicker recovery time than delayed surgery. Both groups had similar death rates (p=0.070). Early laparoscopic cholecystectomy reduced discomfort (p<0.001). Conclusion: This research suggests that early laparoscopic cholecystectomy for acute biliary stone-induced pancreatitis is safe and effective. Early laparoscopic cholecystectomy reduces postoperative discomfort, hospitalization, and complications. Keywords: Early Laparoscopic Cholecystectomy, Acute Biliary Stone, Delayed Laparoscopic Cholecystectomy, Pancreatitis, Biliary Tract Diseases.Top of Form